You Tube como pedagogia cultural: espaço de produção, circulação e consumo de cultura surda - Pinheiro, Daiane (2012)
This research aims to discuss Deaf cultural productions from the media space You Tube, taking such context as a place of education, cultural demarcation, and for the constitution of identities. The culture, in the perspective which I take myself to conduct this work, is crossed by the discursive process and begins to be studied within its social complexity situated in an arena of conflicts generated by the search for meaning and, hence they are part of the games of the relations of power / knowledge. Inserted in these issues I direct it specifically to the virtual environment You Tube, where videos are posted for free access to internet users. The choice of this space to search the materiality of the research is related to the significant cultural content produced and released by deaf people. I seek, on the discourse of difference, to investigate the production strategies of deaf people nowadays, taking the videos here analyzed as output devices. Five videos inserted into two analytical categories were chosen, selected based on a cataloged spreadsheet that allowed a graphic display of the contents of cultural deaf, highlighting the humor and educational issues. Accordingly, the directions that follow in this research guiding the formation of these identities in the context of media and production of meanings is what keeps the deaf cultural difference. In the humoristic Field these meanings are put into circulation by producing representations that operate in contemporary logic, using comedy as a strategy to establish other deaf identities, not less cultural, but perhaps over other truths. In the educational field, these videos tighten the system of inclusive education, identifying such legal actions as a threat to deaf cultural constitution of subjects. These tensions still make sense in these times that the inclusion takes the stage of discussions in contemporary educational policy. Grounded in the field of Cultural Studies in Education, I take the methodological research projects from a posture of suspicion, avoiding immobilization and ready methods, giving malleable directions to the research.